Pattern of oral health practices among dental, basic and post-basic peri-operative student nurses in Benin City, Southern Nigeria - NJBCS, Author (Nigerian Journal of Basic and Clinical Sciences, 2026)
Objective:To evaluate the oral health practices and perception of student nurses in Benin City.Subjects and Methods:A descriptive, cross-sectional survey using a pre-tested self-administered questionnaire with closed-ended questions to collect the data from 1st-year students of dental nurses, basic and perioperative student nurses in Benin City. Data were analysed using the Statistical Package for the Social Sciences version 16.0 withP< 0.05 was considered significant.Results:One hundred and thirty questionnaires were distributed with 112 returned giving a response rate of 86.1%. The participants consisted of three categories of nurses with age range 18–48 years. The mean age of participants was 28.7 years (standard deviation [SD] ±6.80) with those of dental nurses, basic and perioperative nursing students being 23.5 years (SD ± 2.36), 25.2 years (SD ± 3.36) and 36.6 years (SD ± 4.76), respectively. About 80.4% reported always using a toothbrush and fluoride paste out of which the basic student nurses (43%) reported the highest frequency. More than half of the participants (53.6%) brushed their teeth daily, and 76.8% reported taking snacks occasionally. Furthermore, 55.4% had never visited the dentist, with 18.8% visiting within the last 6 months preceding the study and only about a fifth (19.6%) visited for a check-up and 54.5% for scaling and polishing. Furthermore, 41.1% reported having fair oral hygiene.Conclusions:Oral hygiene practices and dental attendance of the student nurses require improvement. Primary oral health should be emphasised in the nursing curriculum, with training in oral examination.